Mountain and Cold Weather Warfighting: Critical Capability for the 21st Century - Pierce, Scott W. (2008)
This monograph posits that military operations in high mountains or intense cold require forces with specialized organization, training, and equipment. The overlap in physical characteristics of mountain and cold weather environments leads to an overlap in the capabilities required of military forces who are able to operate optimally in these regions. The author describes the characteristics of military operations in mountains and cold weather (MCW), and the effects of the MCW environment on each of six warfighting functions. To illustrate the effects of the MCW environment on military operations, the author presents case studies of the cold weather Suomussalmi campaign, which occurred during the Soviet-Finnish Winter War, and the high mountain Kargil campaign, which occurred in the disputed state of Jammu and Kashmir. The latter was one of many bloody confrontations between India and Pakistan. The author also describes those regions that are characterized by high mountains or cold climates that hold strategic importance for the United States. These regions are Central Asia, South Asia, the Caucasus, Iran, the Andes, and the Arctic. The author then catalogs current U.S. military MCW warfighting (MCWW) capabilities, concluding that they are insufficient. Recognizing that the development of a dedicated specialized MCW force is an inefficient and unrealistic goal for the U.S. military, the author recommends a "hedging strategy" to provide a minimally acceptable "off-the-shelf" capability to support U.S. regional combatant commanders. This hedging strategy includes the designation of a Department of Defense executive agent; creation of a high-level programs office to direct and coordinate doctrine, training, and procurement; and the establishment of modern training centers. Finally, the author advocates organizing, training, and equipping specialized units who are designed to provide general purpose forces with MCW-specific expertise and equipment.